THE ACCURACY OF TENSES TRANSLATION IN INDONESIAN NOVEL ENTITLED; DESTINATION UNKNOWN BY AGATHA CHRISTIE - Pangestu, Maulani; Buansari, Istihayyu (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
One of problematic problem in English translation into Indonesian language is tenses. Since Indonesian language is tenseless therefore to make a translation accurate certain method are required. Tenses shall be accurately translated therefore the TL reader understand the original meaning of the ST. Due to that reason, this research aims to investigate furthermore the translation accuracy of tenses in Indonesian novel version entitled; Destination Unknown. The tenses which are found: (1) Simple Present, (2) Simple Past, (3) Simple Future, (4) Present Progressive, (5) Past Progressive, (6) Present Perfect, and (7) Past Perfect. The method used in this study is descriptive analytical-interpretative technique. This study employs questionnaire as the instrument which is given to three raters represents academician, practitioner, and teacher in answering the problems of the study i.e. the translation accuracy of tenses in Indonesian translated novel. In short, the study found that overall all the tenses translation in the Indonesian translated novel was translated accurately. The difference percentages level of accuracy between one tense to another is not quite significant